PELAKSANAAN PEMILU DI INDONESIA BERDASARKAN PERSPEKTIF UNDANG UNDANG DASAR 1945 - Alvianus Kristian Sumual; Mario Gerson Lontaan; Yandi Supit (INTELIGENSIA MEDIA, 2023)
Indonesia is a country that adheres to the Pancasila democratic system where the highest power is in the hands of the people and must be implemented in accordance with the provisions of laws and regulations. That applies. The Dsara Law, which is the highest source of hykum in Indonesia, provides regulations regarding the conduct of elections in article 22 E paragraph 1 on the principle of Direct, General, Free elections. Secret, Honest, and Fair. This research is a type of descriptive research with a literature study method. The results showed that the holding of general elections based on the principles of Direct, General, Free, Secret, honest, and Fair is a manifestation of the democratic values of Pancasila. But now the implementation of uum selection is far from being in accordance with the 1945 Constitution where elections are only a place for power struggles from political elites in Indonesia